1995
DOI: 10.1071/ea9950189
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of annual legume seeds in the wheatbelt of Western Australia

Abstract: The size and composition of pasture legume seedbanks were estimated from 2 surveys on a 460-km west-east transect of the wheatbelt of Western Australia. Survey 1 (in spring) sampled naturalised legumes, and survey 2 (in summer) measured the amount and botanical composition of legume seed from selected sites. Seedbanks were examined in greater detail on 2 farms in the higher rainfall part of the wheatbelt. Survey 2 revealed that mean seedbank size of the poorest 40% of sites (those with 5200 kg seed/ha) was 61 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Imam and Allard 1965, Crawford et al 1998, Green et al 2001 and it is suggested that these populations are more likely to have lower levels of genetic variation within populations because only a limited number of individuals would have contributed to the population (Hamrick 1982, Bennett 1999. Therefore, one reason that the inbreeder T. glomeratum was found to contain higher levels of withinpopulation variation than expected is because the populations were taken from the speciesÕ native environment rather than in colonizing environments where it has previously been studied (Fortune et al 1995, Bennett 1997.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imam and Allard 1965, Crawford et al 1998, Green et al 2001 and it is suggested that these populations are more likely to have lower levels of genetic variation within populations because only a limited number of individuals would have contributed to the population (Hamrick 1982, Bennett 1999. Therefore, one reason that the inbreeder T. glomeratum was found to contain higher levels of withinpopulation variation than expected is because the populations were taken from the speciesÕ native environment rather than in colonizing environments where it has previously been studied (Fortune et al 1995, Bennett 1997.…”
Section: Discussionmentioning
confidence: 99%
“…(hop clover). The naturalized clovers have adapted well to their naturalized environments and have been found to contain relatively large amounts of genetic variation both within and between populations (Fortune et al 1995, Bennett 1997. Although within-population genetic variation is still greater in their native environment (Bennett 1999), some species, such as T. subterraneum, have been shown to contain almost as much variability in Australia as the original Mediterranean populations (Cocks 1992).…”
mentioning
confidence: 99%
“…Naturalised legumes (not commercialised or deliberately sown) are widely distributed and have some adaptive advantages, such as high levels of hardseededness and a small seed size, which promote their persistence under grazing and through cropping phases. Naturalised legumes can comprise the bulk of the pasture seedbank (Fortune et al 1995) although their contribution to herbage biomass production has not been evaluated and quantitative information on the morphology and nutritive value of some species is scarce. The prominence of naturalised species in areas previously sown to commercial species warrants investigation of their value as components of pastures.…”
Section: Introductionmentioning
confidence: 99%
“…M. minima is widely distributed throughout Australia and grows in a wide ecological range (Bennett 1999), while T. arvense is found growing in infertile, sandy soils (Palmer 1972) and may also be widely distributed across Australia (Fortune et al 1995). There seems to be nothing known of the agronomy of M. monspeliaca, while M. minima and T. arvense are usually described as colonising species (Palmer 1972;Cocks 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally the Mediterranean region has also been the centre of domestication and breeding of most of the cultivated species of Trifolium, particularly the perennial clovers, although it can be argued that Australia has also become an important region for Trifolium breeding, with many new species being developed as pasture cultivars (Snowball et al 1992;Nichols et al 1996). In Australia there are also many naturalized species of Trifolium, and a study by Fortune et al (1995) found that wherever they occurred in the wheatbelt of Western Australia they contributed more seed to the seedbank than the sown pasture species. They have become adapted to a wide range of edaphic conditions in southern Australia, due largely to the genetic diversity within each species, even within individual populations (Cocks 1992 in T. subterraneum; Bennett 1997 in T. glomeratum; Bennett 1999 in T. tomentosum).…”
Section: Introductionmentioning
confidence: 99%